2020
DOI: 10.3390/ijerph17124358
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Promotion: A Systematic Review of The Perceptions of Healthcare Professionals

Abstract: Physical activity (PA) is a cost-effective and non-pharmacological foundation for the prevention and management of chronic and complex diseases. Healthcare professionals could be viable conduits for PA promotion. However, the evidence regarding the effectiveness and benefits of the current forms of PA promotion are inconclusive. Healthcare professionals’ perceptions on key determinants impact on the optimum promotion of PA were explored in this review. Thirty-four (34) studies were identified after systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 99 publications
(520 reference statements)
9
93
0
1
Order By: Relevance
“…We need to expand training beyond just HCPs if we are to reduce physical inactivity because it would be dangerous to ‘put all our eggs in one basket’—especially in light of the increasing demands placed on HCPs, including during and after global pandemics. Recent literature [ 57 , 58 ] and stakeholders confirmed such concerns: ‘ We hear a lot from HCPs: it should not just be us trained in this’. We also need to expand PA promotion into other workforces because there could be untapped credible, trustworthy, and wide-reaching PA messengers to help ‘make every contact count’.…”
Section: Discussion—what Now? What Next? Discussing Results Identifying Gaps and Providing Directionsmentioning
confidence: 99%
“…We need to expand training beyond just HCPs if we are to reduce physical inactivity because it would be dangerous to ‘put all our eggs in one basket’—especially in light of the increasing demands placed on HCPs, including during and after global pandemics. Recent literature [ 57 , 58 ] and stakeholders confirmed such concerns: ‘ We hear a lot from HCPs: it should not just be us trained in this’. We also need to expand PA promotion into other workforces because there could be untapped credible, trustworthy, and wide-reaching PA messengers to help ‘make every contact count’.…”
Section: Discussion—what Now? What Next? Discussing Results Identifying Gaps and Providing Directionsmentioning
confidence: 99%
“…Sustained information sharing culture among HCPs could help frontline HCPs such as GPs, to be up to date with PA and PARS information and provide motivation to recommend it to their clients when needed. Therefore, mass promotion of PARS initiatives via primary healthcare interventions supported with printed materials such as pamphlets and diverse media publicity platforms, could enhance the effectiveness of the PARS programme and provide further insights into the roles, benefits, and availability of EP services [37]. Participants also proposed nominating designated PA and PARS specialist in healthcare centres to support GPs, in promoting and coordinating quality care for PARS users.…”
Section: Discussionmentioning
confidence: 99%
“…A purposive sampling strategy (non-random identification and selection of suitable study participants) was used to recruit the participants for this study. This technique included: (1) identification of participants who were a representative sample of the population via a pre-interview survey [36,37]; (2) purposively selecting and contacting respondents who could provide valuable information and represent heterogeneity in the population; and (3) acknowledgment of consent and commitment by participants to take part in the interview.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that physical inactivity (PI) has a substantial influence on obesity, heart disease, hypertension and diabetes, among others. It has become the most serious challenge of global public health in the 21st century [ 3 , 4 , 5 , 6 , 7 ]. The question of how to scientifically and reasonably intervene and improve the physical activity of residents is particularly important for improving the physical health of the general population; it is also of particular importance for the “Healthy China” (HC) strategy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%